Dietary Patterns Derived by Reduced Rank Regression Are Inversely Associated with Type 2 Diabetes Risk across 5 Ethnic Groups in the Multiethnic Cohort. Issue 5 (17th April 2017) - Jacobs, Simone; Kroeger, Janine; Schulze, Matthias B; Frank, Laura K; Franke, Adrian A; Cheng, Iona; Monroe, Kristine R; Haiman, Christopher A; Kolonel, Laurence N; Wilkens, Lynne R; Le Marchand, Loic; Boushey, Carol J; et al.
Abstract: Background: Reduced rank regression (RRR) is an approach to identify dietary patterns associated with biochemical markers and risk of type 2 diabetes (T2D). Objective: We aimed to derive dietary patterns associated with adiponectin, leptin, C-reactive protein (CRP), and triglycerides (TGs) and to examine the prospective associations of these patterns with T2D risk in 5 ethnic/racial groups with differences in T2D rates. Methods: The Multiethnic Cohort (MEC) included 215, 831 African-American, Japanese-American, Latino, Native Hawaiian, and white adults living in Hawaii and California who completed a validated quantitative food-frequency questionnaire in 1993–1996. T2D status was based on self-report with confirmation by administrative data. Serum CRP and TGs and plasma adiponectin and leptin were measured ∼10 y after baseline in a subset ( n = 10, 008) of participants. RRR was applied to dietary data and biomarker information of 10, 008 MEC participants in the combined population and in each ethnic/racial group. RRR-derived dietary patterns, simplified by removal of foods that were not found to be important, were subsequently evaluated for association with T2D risk in 155, 316 cohort members (8687 incident T2D cases diagnosed by 2010) by using Cox proportional hazards regression. Results: Combining ethnic/racial groups, we identified a dietary pattern low in processed and red meat, sugar-sweetened beverages, diet soft drinks, and white rice and high in whole grains, fruit, yellow-orange vegetables, green vegetables, and low-fat dairy that was inversely associated with CRP, TGs, and leptin and positively related to adiponectin. Comparing extreme tertiles, the dietary pattern predicted a 16–28% significantly lower T2D risk in the combined study population and also separately in African Americans, Japanese Americans, Latinos, Native Hawaiians, and whites. Ethnicity-specific derived patterns varied only modestly from the overall pattern and resulted in comparable associations with T2D. Conclusion: This identified dietary pattern may lower T2D risk through its impact on adipokines, by lowering chronic inflammation and dyslipidemia across 5 ethnic/racial groups.